FDG-PET and Neuropsychiatric Symptoms among Cognitively Normal Elderly Persons: The Mayo Clinic Study of Aging - Krell-Roesch, Janina; Ruider, Hanna; Lowe, Val J; Stokin, Gorazd B; Pink, Anna; Roberts, Rosebud O; Mielke, Michelle M; Knopman, David S; Christianson, Teresa J; Machulda, Mary M; Jack, Clifford R; Petersen, Ronald C; et al. (Journal of Alzheimer's disease, 2016)
One of the key research agenda of the field of aging is investigation of presymptomatic Alzheimer's disease (AD). Furthermore, abnormalities in brain glucose metabolism (as measured by FDG-PET) have been reported among cognitively normal elderly persons. However, little is known about the association of FDG-PET abnormalities with neuropsychiatric symptoms (NPS) in a population-based setting. Thus, we conducted a cross-sectional study derived from the ongoing population-based Mayo Clinic Study of Aging in order to examine the association between brain glucose metabolism and NPS among cognitively normal (CN) persons aged > 70 years. Participants underwent FDG-PET and completed the Neuropsychiatric Inventory Questionnaire (NPI-Q), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI). Cognitive classification was made by an expert consensus panel. We conducted multivariable logistic regression analyses to compute odds ratios (OR) and 95% confidence intervals after adjusting for age, sex, and education. For continuous variables, we used linear regression and Spearman rank-order correlations. Of 668 CN participants (median 78.1 years, 55.4% males), 205 had an abnormal FDG-PET (i.e., standardized uptake value ratio < 1.32 in AD-related regions). Abnormal FDG-PET was associated with depression as measured by NPI-Q (OR = 2.12; 1.23-3.64); the point estimate was further elevated for APOE ɛ4 carriers (OR = 2.59; 1.00-6.69), though marginally significant. Additionally, we observed a significant association between abnormal FDG-PET and depressive and anxiety symptoms when treated as continuous measures. These findings indicate that NPS, even in community-based samples, can be an important additional tool to the biomarker-based investigation of presymptomatic AD.
Keywords: Cross-Sectional Studies; Male; Aging; Cognition; Brain; kognitivní dysfunkce; Positron-Emission Tomography; pozitronová emisní tomografie; psychomotorický neklid; Aged; mužské pohlaví; senioři; deprese; Cognitive Dysfunction; Neuropsychological Tests; úzkost; senioři nad 80 let; fluorodeoxyglukosa F18; kognice; lidé; ženské pohlaví; apolipoproteiny E; Fluorodeoxyglucose F18; Humans; stárnutí; průřezové studie; mozek; Aged, 80 and over; Psychomotor Agitation; neuropsychologické testy; psychiatrické posuzovací škály; Female; Depression; Psychiatric Status Rating Scales; Anxiety; Apolipoproteins E